Dermatophytoses in children: study of 137 cases - FERNANDES, Nurimar C.; AKITI, Tiyomi; BARREIROS, Maria da Glória C. (Revista do Instituto de Medicina Tropical de São Paulo, 2001)
Dermatophytoses are common fungal infections caused by dermatophytes but there are few data about this condition in the childhood. 137 children below the age of 12 and clinically diagnosed as tineas were investigated prospectively at Instituto de Puericultura e Pediatria, Rio de Janeiro, from 1994 to 1999. Hair, skin/nails scraping and pus swabs were collected from lesions and processed for fungus. Male children from 2 to 12 years were mostly affected; tinea capitis (78 cases) mainly caused by Microsporum canis (46 cases) was the most common clinical form. Tinea corporis (43 cases) mainly caused by Trichophyton rubrum (17 cases) accounted for the second most frequent clinical form. Tinea cruris (10 cases) with Trichophyton rubrum (5 cases) as the most common etiologic agent accounted for the third most frequent clinical form. Tinea pedis and tinea unguium were much less frequent (3 cases each). Trichophyton rubrum was the most common etiologic agent isolated in these cases (3 cases).